(untitled) (Research, Society and Development, 2023)
Objective: To analyze the epidemiologic profile of patients suspected of developmental dysplasia of the hip (DDH) in Rio Grande do Sul, correlating to the clinical and radiological diagnosis of the pathology. Methods: A cross-sectional observational study executed by the Orthopaedic and Traumatology service from a philanthropic hospital in Rio Grande do Sul. Epidemiologic data had been collected, clinical radiological diagnosis of pediatric patients suspected of DDH assisted from 2016 to 2021 in that unit had been analyzed. Results: 85 patients were included in the study, the analysis of the epidemiologic profile shown a predominance of the female gender and caucasian ethnicity, standing out in cesarean sections. When comparing the physical examination to the radiograph or ultrasound, it wasn’t observed any statistically significant association (p>0,05). When comparing the radiograph to ultrasound, there also wasn’t any matching between them (p>0,05). Conclusion: The clinical exam it is considered the most efficient of screening and diagnosis methods. Complementary exams such as radiograph and ultrasound are fundamental to situations in which diagnostic suspicions are maintained. However, those tests shouldn’t be evaluated isolated, as the evaluation with only one method decreases the diagnosis accuracy.